Leading article: A meta-reflection on my emerging as a scholar of action research - du Toit, P.H. (South African Journal of Higher Education, 2018)
The self-enquiry reported in this article is conducted at a meta-level of meaning making. A meta-level of reflection is typical of a meta-cognitive mind-set; it entails reflecting on my reflection from a scholarly point of view. The theory on whole brain thinking informs the conceptual framework for my research and teaching practice; therefore I have given new meaning to action research as being whole brain action research, reflection as whole brain reflection, and for the purpose of this article specifically, whole brain meta-reflection. My scholarly reflections focus on what is reported in publications. Data sets gathered over the years are not reported per se as it has already been made public. Instead, I reflect at macro level on existing data. What is made public by means of this article is my reflection on my reflections in the past. It is inevitable that the raw data I have drawn from forms the core of my article. Therefore, a great number of references indicate me as author or co-author.